THE USE OF THE THERAPEUTICAL ULTRASOUND IN THE CALCANEAL TENDON AIMING THE INCREASE OF THE AMPLITUDE OF MOVEMENT (Fiep Bulletin - online, 2015)
This work had as objective to prove the effectiveness of the therapeutical ultrasound in the increase of amplitude of movement of ankle dorsiflexion. The calcaneal tendon was chosen as object of the research, which had its superficial anatomical seating, facilitating the absortion of the ultrasonic waves. The study had the participation of 15 volunteers. The average of increase of movement was 3,6º.
Keywords: Ultrasound; Calcaneal tendon; Ankle joint